USAINS HOLDING READY TO ASSIST USM IN FACING FUTURE FINANCIAL CHALLENGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 December 2015 – Established in 17 December 1998 by Universiti Sains Malaysia (USM), Usains Holding Sdn. Bhd has since served as its business arm and will continue to assist the university when the university faces a reduction in government funding in the future.